Phytochemicals Mediate Autophagy Against Osteoarthritis by Maintaining Cartilage Homeostasis - Tian, Zheng; Zhang, Xinan; Sun, Mingli (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a common degenerative joint disease and is a leading cause of disability and reduced quality of life worldwide. There are currently no clinical treatments that can stop or slow down OA. Drugs have pain-relieving effects, but they do not slow down the course of OA and their long-term use can lead to serious side effects. Therefore, safe and clinically appropriate long-term treatments for OA are urgently needed. Autophagy is an intracellular protective mechanism, and targeting autophagy-related pathways has been found to prevent and treat various diseases. Attenuation of the autophagic pathway has now been found to disrupt cartilage homeostasis and plays an important role in the development of OA. Therefore, modulation of autophagic signaling pathways mediating cartilage homeostasis has been considered as a potential therapeutic option for OA. Phytochemicals are active ingredients from plants that have recently been found to reduce inflammatory factor levels in cartilage as well as attenuate chondrocyte apoptosis by modulating autophagy-related signaling pathways, which are not only widely available but also have the potential to alleviate the symptoms of OA. We reviewed preclinical studies and clinical studies of phytochemicals mediating autophagy to regulate cartilage homeostasis for the treatment of OA. The results suggest that phytochemicals derived from plant extracts can target relevant autophagic pathways as complementary and alternative agents for the treatment of OA if subjected to rigorous clinical trials and pharmacological tests.